Analisis Surplus-Defisit Air Daerah Irigasi Gondang Kabupaten Lamongan - Fatimah, Ratna Siti; Affandy, Nur Azizah; Kartikasari, Dwi (Jurnal Talenta Sipil, 2024)
Population growth in Indonesia has increased by an average of 1.25% from the previous population every year from 2020 to July 2022 (Badan Pusat Statistik, 2022). Population growth is in line with increasing food needs, where development in agriculture is one of the priorities in building food security in the future. Lamongan Regency contributed 564,139 tons of rice in 2020 and was nominated for 5 (five) largest major contributors at the national level (Redaktur Jatim, 2021). High population growth and increasing food demand require adequate infrastructure, including efficient irrigation systems. The balance of available irrigation water and required water determines success in irrigation water management. This study aims to analyze reliable water discharge using the F.J. Mock method, calculating plant needs to determine water surpluses. This research was conducted in the Gondang Irrigation Area located in Sugio District, Lamongan Regency. The area of gondang irrigation area is 10588 ha. From the results of the study, the highest discharge occurred in 2013, in April period II amounting to 77.71 m3 / s. The water needs of plants experience water shortages for 3 months (July-September).